NEW ZINC OXALATO AND HYDROGENOXALATO COMPLEXES: SYNTHESIS AND INFRARED STUDY - GORGUI AWA SECK; LIBASSE DIOP; ABOUBACRY SENE (Journal of Engineering Studies and Research)
Five new oxalato and hydrogenoxalato complexes with ZnBr2 have been synthesized and studied by infrared. Discrete structures have been suggested in the basis of spectroscopic data. The environments around the zinc centre being trigonal bipyramidal, tetrahedral, octahedral or monocapped octahedral. The anions behave as monochelating ligands. When the cations and OH group are involved in extra hydrogen bonds, a supramolecular architecture may be obtained.